Cerebral Palsy : A Literatur Review - Lale Nandita Hulfifa; Baiq Annisa Salmaadani Syafitri; Carolina Janicca Winda Manafe; Zhafirah Amany; Zirly Vera Aziri; Syahla Marsellita Wahyudi; Anak Agung Bagus Tito Indra Prawira Negara; Muhammad Abdurrosyid; Muhammad Azim Billah; Dinie Ramdhani Kusuma; Afifah, Fiza (Jurnal Biologi Tropis, 2024)
Cerebral Palsy is a non-progressive damage that occurs in the brain tissue of a fetus or infant during development. CP is a disease that occurs worldwide, with approximately 1 to 4 children out of 1,000 live births having CP in population study data covering the entire world. CP is one of the most common causes of motor disability in children. Prompt diagnosis and appropriate treatment can promote a better prognosis for the patient. The writing of this article aims to add information related to CP so that early detection can be done and how CP therapy can improve the quality of life of people with CP. The research method used is a type of literature review that discusses the definition, etiology, epidemiology, pathophysiology, how to diagnose to management of cerebral palsy. Data sources were retrieved by conducting electronic searches through library search sites including PubMed, ProQuest, ScienceDirect, MDPI and Google Scholar.